Reconsidering PAPER CUPS: Waste to value-added products - Avni Kothari; Veena Dhayal (Environmental Challenges)
In today's environmentally conscious world, waste management and recycling are critical, especially for paper cups, which are ubiquitous in coffee shops, offices, and events. After the ban on plastic cups in many countries, the market for paper cups has seen a sudden spike. Although considered as a greener alternative than plastic cups, the recycling of paper cups possess a significant challenge due to the inner plastic lining, which makes the separation and recycling process more complex. Consequently, most of the used paper cups end up in the landfills, contributing to environmental pollution, resource depletion and causing a problem in the recycling of other paper-based items. The production of paper cups also has a substantial environmental footprint, involving deforestation, high water and energy consumption, increased carbon footprint and greenhouse gas emissions. Innovations in recycling technologies, such as biodegradable and compostable materials, and advanced facilities capable of separating plastic liners from paper, are emerging. But the success of these initiatives will require manufacturers to create more recyclable cups, consumers to treat and dispose of them appropriately, recycling facilities to invest in upgraded processes, and policymakers to back their efforts by enacting supportive regulations.